2017
DOI: 10.2495/eq-v2-n1-70-80
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise analysis of gasification reactions with aspen plus and CPFD

Abstract: The energy from biomass can be utilized through the thermochemical conversion processes of pyrolysis and gasification. Biomass such as wood chips is heated in a gasification reactor to produce a synthesis gas containing CO, H 2 and CH 4 . The gas can be further processed to bioproducts or fuels. The thermochemical process involves devolatilization of wood followed by steam gasification, CO 2 gasification, methanation, water gas shift reactions and methane reforming. To optimize the performance of the reactor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The complexity and dimensions of the model are also increased with the desired model outputs, that is, with more detailed reaction kinetics and reactor hydrodynamics. However, because it has been frequently reported that the complex solid-fluid contact patterns of fluidized bed gasifiers may result in larger deviations from ideal equilibrium compositions (and ideal mixing), kinetic-hydrodynamic modelling is a particularly common approach chosen for modelling fluidized bed gasifiers, as argued by several authors [25,28,37,38,42,51,54,56,64]. The promise of potentially more accurate results motivates about 34% of the researchers who model gasification to employ simulations that model the kinetics of key reactions (see Fig.…”
Section: Kinetic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexity and dimensions of the model are also increased with the desired model outputs, that is, with more detailed reaction kinetics and reactor hydrodynamics. However, because it has been frequently reported that the complex solid-fluid contact patterns of fluidized bed gasifiers may result in larger deviations from ideal equilibrium compositions (and ideal mixing), kinetic-hydrodynamic modelling is a particularly common approach chosen for modelling fluidized bed gasifiers, as argued by several authors [25,28,37,38,42,51,54,56,64]. The promise of potentially more accurate results motivates about 34% of the researchers who model gasification to employ simulations that model the kinetics of key reactions (see Fig.…”
Section: Kinetic Modelsmentioning
confidence: 99%
“…[25,37,56]), Kin-total (e.g. [27,28,38,52,64,72,73,81,83,85]), and Ki/Eq (CRF) (e.g. [31, 40-42, 58, 121]) approaches.…”
Section: Kinetic Modelsmentioning
confidence: 99%
“…After pyrolysis, RGibbs is applied for simulation of the biomass gasification. This reactor computes the syngas composition by minimizing the Gibbs free energy based on complete chemical equilibrium assumption [57][58][59][60][61]. Input streams to the RGibbs are decomposed biomass and air then combustion and reduction reactions will be occurred inside of the reactor.…”
Section: Figure 1 Modules and Streams Of Gasification Simulated In Aspen Plusmentioning
confidence: 99%